2022
DOI: 10.1002/ppap.202200121
|View full text |Cite
|
Sign up to set email alerts
|

Plasma polymerization for biomedical applications: A review

Abstract: Plasma polymers have long been of interest as thin film coatings on biomedical devices and products, to generate desirable surface properties for favorable biointerfacial interactions. Plasma polymers have also been used as platforms for the covalent immobilization of bioactive molecules. More recently, additional aspects have been investigated, such as selective prevention of adhesion of microbial pathogens, either via plasma polymers per se or including antimicrobial drugs. Plasma polymers have also been inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 145 publications
(206 reference statements)
0
9
0
Order By: Relevance
“…[70] From the above assessment, mainly C 2 H 2 and C 2 H 4 are well-suited polymerizable monomers used, for example, to deposit hard coatings or diffusion-controlling layers. [71][72][73] However, they do not bear interesting functionalities, which is why they are also mixed with nonpolymerizable gases such as N 2 , NH 3 , CO 2 , CO, H 2 O, O 2 , and so on, to incorporate functional groups in a cross-linked hydrocarbon matrix. Importantly, the threshold energy for the hydrocarbon molecules, as derived from the Arrhenius-like approach, was found to be retained independent of the gas admixture.…”
Section: Plasma Polymerizationmentioning
confidence: 99%
“…[70] From the above assessment, mainly C 2 H 2 and C 2 H 4 are well-suited polymerizable monomers used, for example, to deposit hard coatings or diffusion-controlling layers. [71][72][73] However, they do not bear interesting functionalities, which is why they are also mixed with nonpolymerizable gases such as N 2 , NH 3 , CO 2 , CO, H 2 O, O 2 , and so on, to incorporate functional groups in a cross-linked hydrocarbon matrix. Importantly, the threshold energy for the hydrocarbon molecules, as derived from the Arrhenius-like approach, was found to be retained independent of the gas admixture.…”
Section: Plasma Polymerizationmentioning
confidence: 99%
“…PECVD has also been employed as a method to enhance the resistance of biomaterials to degradation [89]. It has been demonstrated that PECVD of biocompatible diamond-like carbon (DLC) on metal surfaces reduces corrosion, making such coatings suitable for metal implants [90,91].…”
Section: Pecvdmentioning
confidence: 99%
“…[ 10 ] Plasma polymerization introduces specific functional groups to the surface such as amines, carboxylic acids, aldehydes, and esters through the use of relevant volatile monomers. [ 11 ] Coupling agents such as carbodiimide and N ‐hydroxysuccinimide [ 12 ] react with these functional groups to covalently bind the biomolecules to the surface. Both aminosilanization and functional groups addition through plasma polymerization are time‐consuming processes with multiple steps.…”
Section: Introductionmentioning
confidence: 99%